Business Development Strategies of Culinary MSME Based on Islamic Economic Principles - Hikmah, Durrotul; Rohman, Afifur; Rahmawati, Lilik (LifeSciFi, 2025)
Indonesia’s rich culinary diversity not only represents cultural and historical identity but also constitutes a strategic economic sector that significantly contributes to the national gross domestic product and employment, particularly through micro, small, and medium enterprises. This study aims to analyze the integration of Islamic economic principles in the business development strategy of the culinary MSME restaurant. A qualitative phenomenological approach was employed to explore the lived experiences underlying the implementation of these principles. Data were collected through in-depth interviews with two employees and seven customers, supported by observations and document analysis. The findings indicate that the consistent internalization of Islamic economic principles functions not only as an ethical foundation but also as a strategic resource that enhances business sustainability. The principle of justice is reflected in fair and timely employee compensation and affordable pricing, honesty is manifested through transparency in raw materials and pricing, and halal principle is implemented across the production and supply chain. These practices foster trust, employee engagement, customer loyalty, and strengthen intangible assets such as reputation and value-based branding. The study implies that Islamic economic principles can serve as a viable strategic framework for culinary MSMEs when combined with adaptive management and innovation.